Keberlakuan Klausula Security Exceptions Dalam Perjanjian Trade-Related Aspects Of Intellectual Property Rights (Trips) Di Masa Pandemi Covid-19 - Putra, Daniel Nicholas; Dewi, Yetty Komalasari, YKD (Jurnal Hukum & Pembangunan, 2021)
WTO commitments, particularly related to intellectual property rights in the TRIPS Agreement, could potentially hinder efforts to increase access to medicines and vaccines during the Covid-19 pandemic. In time of emergency, these commitments can be overridden using the WTO security exceptions clause. This article compares the WTO security exceptions to general exceptions in Article XX of the GATT 1994 and non-precluded measures in the Argentina-US BIT, India-Germany BIT, and India-Mauritius BIT, and analyses how the Covid-19 pandemic can be a valid reason to waive the obligations under the TRIPS Agreement using the security exceptions clause. In particular, this article discusses how this pandemic has resulted in an “emergency in international relations” and the waiver of obligations in the TRIPS Agreement for public health and safety qualify as “essential security interests”.